Ringing in the Changes: The Implications of the new regulations for the colleges. - Norma V Paverd (AOSIS, 1985)
In particular, the objective of this presentation is to describe • how the college structure and function will alter to enable the implementation of the new regulation • the concept of autonomy and the legislation which has been passed in the Cape allowing autonomy • give some indication of how the student's position will change.